Learn from the Experts about Being Performance-First Tom Barker - Barker, Tom (O'Reilly Media, Inc., 2018)
In this interview, Ally MacDonald talks to Tom Barker about how companies can make the shift to being "performance-first" at both a technical and organizational level. Tom Barker is a software engineer, an engineering manager, a professor and an author. Currently he is Director of Software Engineering and Development at Comcast, and an Adjunct Professor at Philadelphia University